EL ‘PRECEDENTE JUDICIAL’: UNA FIGURA AJENA AL SISTEMA COLOMBIANO DE FUENTES DEL DERECHO (2016)
The analysis of the issue of “judicial precedent” or “jurisprudence”, in the light of the relevant constitutional and legal norms, the jurisprudence of the Constitutional Court and designated by two (2) indoctrinators, whose authority on the subject is widely recognized doctors Diego Eduardo López Medina and Carlos Bernal Pulido - has allowed me to conclude, as I intend to demonstrate in this essay, this figure is alien to the legal policy of the Colombian State organization and judicial practice in the it develops.The strong influence of common law in our legal system and constitutional interpretation makes judges today link their decisions not only legal content, but the decisions of senior judges especially human rights, and structuring a new form of understand the law, grounded, not in the positivist model, but through systematic interpretation by the court on the rights and especially those enshrined in the constitution itself, applying criteria of fairness and proportionality to be applied in the solving future cases.It is sufficient to observe the definition of “judicial precedent” to note that this figure does not fit the system design sources in Colombian law “in which only gives the jurisprudence character supplementary source formal law, as well as auxiliary criteria of judicial activity; so that in a legal-political system in which judicial decisions are extra formal source of law and criteria guiding non-binding judicial activity, the quality of main formal source of law and binding judgment of the work of judges, which the Constitutional Court has granted its doctrine on human rights contained in the review sentences fault protection, as well as the constant jurisprudence of the so-called High Courts, it lacks legal support.